Formulation and evaluation of natural anti Candida albicans ointment containing mango leaf (Mangifera indica L.) extract - Dian Riana Ningsih,; Purwati,; Zusfahair,; Filliani Akanadewi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Arumanis mango is one of plants potentially used as a medicine. Arumanis mango leaf is potentially used as antimicrobial, which are as antibacterial and antifungal. Mango leaf extracts are able to inhibit Candida albicans with inhibition zone of 8.12 mm. The use of extracts for various purposes has disadvantages. This research aims to formulate ointments dosage from mango leaf extracts, to know its physical properties and its activity against Candida albicans. Antifungal activity test is conducted using diffusion method. The fungus used is Candida albicans. The absorbent ointment preparations has homogeneous semisolid form, yellowish white color, and distinctive odor. The ointment preparations has dispersive power value of 4.90-6.23 cm, adhesiveness of 2.0-7.0 seconds, pH value of 6.56-6.99 and able to protect skin from the outside environment. Inhibition zone of absorbent ointment with concentrations of 30, 65, and 125 ppm, respectively, was 3.07; 5.96; and 9.51 mm.